Prenatal exposure to benzodiazepines and the development of the offspring – a systematic review - Jensen, Anne Grosbøl; Knudsen, Signe Schöllhammer; Bech, Bodil Hammer (Neurotoxicology and teratology, 2022)
To summarize the available literature on long-term-development of children exposed to benzodiazepines in utero, through a systematic review. We conducted a systematic literature search of PubMed, PsycINFO and embase (1/9–2020 to 3/9–2020). We included original studies with children older than one year prenatally exposed to BZ's and Z-hypnotics with outcomes regarding all psychological-, social-, motor- and neurodevelopmental disorders or disturbances of the children. Studies without a BZ-unexposed comparison group were excluded. Studies with only a single-dose exposure, conference abstracts, case reports and case series were excluded. The intern validity of the included studies was assessed with the Newcastle Ottawa Scale tool (NOS). 13 cohort studies were included in this systematic review. The outcomes investigated were internalizing and externalizing problems, language, hearing and communication skills, neurological outcomes and motor function, behavioral and emotional problems, social skills, intellect and academic achievements, psychiatric diagnoses and overall development. We found some evidence of higher risk of developing internalizing problems, impaired gross motor skills, lower academic achievements and increased ADHD-traits among children exposed to benzodiazepines in utero. Prenatal exposure to benzodiazepines were associated with 4 developmental outcomes indicating an impaired long-term-development of the offspring. However, results were contradicting, and it cannot be ruled out, that findings might be due to bias. Furthermore, it remains uncertain if the results are of clinical relevance and whether developmental problems persist in later childhood. This study revealed a clear need for further research in the subject. •Benzodiazepines cross the placenta barrier and might influence on child outcome.•Found some evidence of altered development in specific outcomes, but literature is sparse.•Prenatal use of benzodiazepines is not considered a major risk factor for altered neurodevelopment in early childhood.